Web-based e-Learning system science year one explore science and math / Sandhya Hari Mohan Ratti - Sandhya Hari , Mohan Ratti (2004)
Explore Science & Math system is a Web-based e-Learning System Science for Year one students. The e-Learning system enables the users to access Science Year One syllabus as an alternative process in learning. The Explore Science & Math System refers to a well-designed set of interactions with sufficient contents of notes, exercise, quiz and revision activities. Games are included to create potential creative skills and understanding. Besides, there is an animated genie to guide and make the learning environment more fun and interesting. The e-learning system as a learning tool is developed based on increment development model. Functional and non-functional requirements of this system discussed to ensure system requirements are delivered efficiently so system functionality is available earlier. Basic technologies concept of the system for example ASP, Microsoft FrontPage and Flash MX and Adobe Photoshop 7.0 are selected in the system development. The features of Explore Science & Math System such as user friendly, easy to navigate, interactive and modularity is flexible enough to allow for different learning paths on learning styles and abilities for the users.